Pengembangan Modul Berbasis Potensi Lokal pada Materi Ekosistem sebagai Bahan Ajar di SMA N 1 Tanjungsari, Gunungkidul - Dytta Lyawati Prabowo; Nurmiyati Nurmiyati; Maridi Maridi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The aims of this research were: 1) To develop local potential-based module, 2) To determine the feasibility of the local potential-based module on ecosystem subject matter. This research was research and development (RnD. The population of this study was the whole grade X class of SMA N 1 Tanjungsari academic year 2015/2016. Samples were taken by using cluster sampling technique. Samples were determined by balance test. The research procedure refers to modified Borg & Gall 7 stages technique: 1) research and information collecting; 2) planning; 3) develop preliminary form of product; 4) preliminary field testing; 5) main product revision; 6) main field testing; and 7) operational product revision. The results showed that 1) local potential-based module has been developed according to Borg & Gall procedures arranged by involving several local potential in the area Gunungkidul and research results from local phenomena, 2) the feasibility of potential-based module qualified as "very decent" by the subject matter experts,  the module development and grammar expert, the design expert, the cognitive test development experts, the students and practitioners (teachers). The conclusion of this research is local potential-based module feasible for use as teaching on ecosystem subject matter of SMA N 1 Tanjungsari, Gunungkidul.Keywords         : Local Potential-based Module.